(untitled) (Journal of Pharmaceutical Negative Results, 2023)
This work deals with the study of Benzyl(3-fluoro-4-morpholinophenyl)carbamate with the help of Density Functional Theory (DFT) calculations. The B3LYP method with 6-311++G(d,p) and cc-pVDZ basis sets are used in DFT calculations. The structural parameters (Bond length and Bond Angle) of the titled molecule are calculated theoretically by DFT. The thermodynamic parameters (Heat capacity, Entropy and Enthalpy) are calculated for temperatures between 100 to 1000 Kelvin. The hybridization and covalent effects are investigated using Natural Bond Orbital (NBO) calculations with the help of the charge delocalization energies and hyperconjugative interactions. The Non-linear optical (NLO) properties of the molecule are calculated by DFT using 6-311++G(d,p) and cc-pVDZ basis sets. The Fukui function is used as a local density functional descriptor to model chemical reactivity and site selectivity.